Meeting development goals: evidence from the Civil Society Education Fund. Issue 6 (18th August 2017) - Rambla, Xavier; Verger, Antoni; Edwards, D. Brent; Fontdevila, Clara; Bonal, Xavier
ABSTRACT: In recent years, the Civil Society Education Fund has supported national education civil society coalitions (NECs) in low-income countries so that they put pressure on governments and donors to implement the Education for All agenda and the Millennium Development Goal on education. This article draws on literature on global governance as well as on an extensive evaluation of the CSEF to explore the actual contribution of this initiative to the activity of NECs. The article highlights the achievements and shortcomings of the CSEF and includes a set of practical recommendations on the role of global civil society in international development processes.